Exploration on tribological behaviours of perrhenates as potential lubricating oil additive during a wide temperature range. (21st April 2015) - Wang, Junhai; Liu, Yang; Duan, Deli; Li, Shu
Abstract The perrhenates of calcium, copper and lead used as oil additive were synthesised by using the aqueous solution method. The tribological properties of these perrhenates were examined by using a ball‐on‐disc tribotester during a wide temperature range and a four‐ball testing machine at room temperature. The four‐ball test results showed that all synthesised perrhenates presented good extreme pressure property to a certain degree and demonstrated satisfactory wear resistance at room temperature. The ball‐on‐disc experiment results showed that the base oil with perrhenate additives significantly decreased friction and wear compared with pure base oil at elevated temperatures. An antifriction and low‐shear layer was verified to form on sample surface after testing under high temperature. This layer effectively prevented the direct contact of sliding surfaces and decreased the friction coefficient. The antifriction behaviour of perrhenates implied that they could be developed as the candidate of oil additives for a hybrid lubricating mode. Copyright © 2015 John Wiley & Sons, Ltd.